The effect of high cholesterol level on recurrence rate of oral ulcer - Mustafa Al-Ahmad, Basma Ezzat; Abdul Qader, Omar Abdul Jabbar; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon (2018)
Introduction: Oral ulcers are one of the most common complaints of the oral mucosa lesion. Ulcer is defined by damage or discontinuity of the epithelium and lamina propria which usually affects the non-keratinized or poorly keratinized surfaces of the oral mucosa. It is a multifactorial condition several predisposing factors have been suggested. Objectives: The aim of this study is to determine the relationship between the increase in cholesterol level and the presence of recurrent oral ulcer. Materials and Methods: A case control study was conducted in oral medicine clinic Kulliyyah of Dentistry International Islamic University Malaysia, Kuantan, Pahang. Convenience sampling was used to select the sample devided into 2 groups patient with recurrent oral ulcer (ROU) (male and female) and control. Patients who fulfilled the criteria were selected. Blood cholesterol and blood pressure of both groups were mesured and recorded. Data analysis was done using independent t-test by, SPSS version 20 for Windows. Results: Cholesterol level was significantly higher in patient with recurrent oral ulcer (6.32 +/- 0.45mmol) compared to control group (4.97 +/- 0.28mmol) (p<0.05). t(46) = 2.75, p = 0.008. It is also found that the control group had statistically significantly lower S.BP (113.77 +/- 2.93 mmHg) compared to the subject group (126.62 +/- 3.61 mmHg), t(46) = 2.75, p = 0.008. Conclusions: This study emphasizes that high cholesterol level is highly associated with ROU.